Formulation and Sensory Evaluation of Crystal Candy Containing Collagen Extract from Milkfish (Chanos chanos) Scale Waste - Fauzi, Ach Zakyah Al; Priyoherianto, Andri; Fitriany, Erna (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2026)
Stunting remains a major public health issue in Indonesia, with a prevalence of 21.6% in 2023, primarily caused by chronic nutrient deficiencies. While collagen does not directly address all nutritional causes of stunting, its protein content may contribute to improving dietary quality. This study aimed to develop a functional crystal candy formulation incorporating collagen extracted from milkfish (Chanos chanos) scale waste as a potential source of protein supplementation.  Collagen was extracted through maceration using 0.05 M NaOH for 8 hours, followed by hydrolysis in 0.3 M acetic acid for 72 hours, heating in a water bath, and drying at 50°C. The extraction yield was 18%, with the presence of amino compounds confirmed through the ninhydrin assay. The extracted collagen was incorporated into crystal candy formulations at concentrations of 0% (F1), 5% (F2), and 10% (F3). Physical quality was evaluated through organoleptic, pH, and hedonic sensory tests involving 80 panelists. The F2 formulation demonstrated the highest sensory acceptability, with an average pH of 6.32. This study provides preliminary data on the feasibility of utilizing fish scale waste as a functional ingredient in confectionery products; however, further analyses of nutritional content, collagen bioactivity, and storage stability are required to substantiate its potential health benefits.